Census Technology, Politics, and Institutional Change, 1790–2020. - Ruggles, Steven; Magnuson, Diana L (Journal of American History, 2020)
The article focuses on the history of the United States (U.S.) census between 1790 and 2020. Topics include the data capture and processing technology for the U.S. census, the federal response to various technical challenges experienced over the centuries, and the political aspects of census demographics.